Determination of optimum irrigation scheduling for sorghum in Benna-Tsemay Woreda, Southern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
Scarcity of water is the most severe constraint for sustainable development of agriculture in arid and semi-arid areas. Hence, novel irrigation water application systems need to be developed so that high crop yield and water productivity per unit of land can be increased. Thus, the field experiment was conducted with the objective of determining the effect of different soil moisture depletion levels on yield and water use efficiency of sorghum crop in Benna-Tsemay woreda at Enchete kebele, Southern Ethiopia. The experiment was conducted for two consecutive years (2019-2020). It was arranged in RCBD with three replications and treatment was rated for five levels of available soil moisture depletion (ASMD), where T1 = 60%, T2 = 80%, T3 = 100%, T4 = 120%, and T5 = 140% of ASMD. Analysis of variance has shown that yield and water use efficiency of sorghum crop was significantly (P < 0.05) affected by irrigation scheduling. As observed in this study, the most economically attractive and environmentally accepted for small scale farmers with tolerable cost of production and higher net benefit was obtained by application of T3 (100% ASMD) under conventional furrow irrigation system. Therefore, for this particular sorghum crop (teshale variety), it could be concluded that increased water saving and water productivity through irrigation at 100% ASMD under conventional furrow irrigation system can solve the problem of water shortage and would ensure the opportunity of further irrigation development in the study area and similar agro-ecology.Int. J. Agril. Res. Innov. Tech. 11(2): 95-102, Dec 2021